Suppressing circ_0008494 inhibits HSCs activation by regulating the miR-185-3p/Col1a1 axis - Li, Binbin; Zhou, Jiaming; Luo, Yuanyuan; Tao, Kegong; Zhang, Lifen; Zhao, Ying; Lin, Yong; Zeng, Xin; Yu, Hongyu (Frontiers in Pharmacology, 2022)
Background: Hepatic fibrosis (HF) is characterized by activation of hepatic stellate cells (HSCs) and extensive deposition of extracellular matrix components, especially collagens. However, effective antifibrotic therapies are still lacking. Recently, circular RNAs (circRNAs) have been identified as novel regulators of HF. Methods: circRNAs profile was screened by RNA sequencing and the location of circ_0008494 was confirmed by fluorescence in situ hybridization assay in human HF tissues. Bioinformatics analysis was used for result prediction and dual-luciferase reporter, together with AGO-RIP and biotin-coupled miRNA capture assays, were used to determine miR-185-3p/collagen type I alpha 1 chain (Col1a1) as the target of circ_0008494. A stable circ_0008494-interfering human HSCs cell line was constructed and used to determine the regulatory mechanism of circ_0008494/miR-185-3p/Col1a1 axis. Results: circ_0008494 was abundantly and significantly over-expressed in human HF tissues and located at the cytoplasm of HSCs. Together, dual luciferase reporter, AGO-RIP and biotin-coupled miRNA capture assays confirmed that circ_0008494 acted as a sponge of miR-185-3p. Cell functional experiments and rescue assays demonstrated suppressing circ_0008494 could inhibit activation, proliferation, migration of HSCs and promote their apoptosis through miR-185-3p. In particular, the HF indicator, Col1a1, was validated as the direct target of miR-185-3p and the suppression of circ_0008494 inhibited the expression of Col1a1 by releasing miR-185-3p. Conclusions: Knocking down circ_0008494 inhibited HSCs activation through the miR-185-3p/Col1a1 axis. circ_0008494 could be a promising treatment target for HF.